Consultation Response : Terrorism Act 2000 : Paragraph 3(4) of Schedule 8 : Video recording with sound Code of Practice.: Terrorism Act 2000 : Paragraph 3(4) of Schedule 8 : Video recording with sound Code of Practice. (2020) - Great Britain., Northern Ireland Office,
No abstract available